TEACHER OBSTACLES IN IMPLEMENTING THE INDEPENDENT CURRICULUM AT SMP 4 MEULABOH - Surya Darma Bakti; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The curriculum is constantly changing according to the needs of society and technological advancements. The purpose of this study was to find obstacles in the implementation of the independent curriculum at SMP 4 Meulaboh and teacher readiness problems based on teacher knowledge and skills. In this study, descriptive analysis methods were used, and data were collected through interviews, documentation, and literature studies to supplement the statements made by interviews. The results showed that SMP 4 Meulaboh still faces challenges in implementing the independent curriculum. This is because they do not receive special training on the independent curriculum, so they do not know how to make subject matter. This research shows that teachers are not ready and are still confused to implement an independent curriculum because they do not understand how to find learning materials or media in the process of teaching and learning activities that are in accordance with the independent curriculum. More senior teachers also face difficulties in finding learning materials or media in the process of teaching and learning activities that are in accordance with the independent curriculum.